(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
After the Ilinden’s uprising in 1903, the neighboring Balkan states did change the means of propaganda’s activities. Previous ecclesiastical and cultural-educational activities were transformed into military actions with the engagement of armed bands. SMORO had resisted on those activities, not permitting existence of other foreign bands in Macedonia. Such situation evolved into open armed conflict between the armed units of SMORO and foreigner propaganda’s armed units. The consequences of such battle were disastrous not only for local Macedonian population, but for Macedonian liberation movement, as well. In 1904, with direct support of Serbian authorities, first Serbian armed bands, composed of local persons, appeared in Ottoman Macedonia. Such Serbian bands, led by Mitsko Krstevski, in October 1904 managed to took in captivity one of the most prominent leader of SMORO, the wounded Damian Gruev. However, after serious threats which were made by SMORO, Serbs did not dare to hand over Damian Gruev to the Ottoman authorities or to execute him. After one month long captivity Damian Gruev was released. This event was used by Serbian propaganda in Macedonia for self promotion.